Optical mapping study of blebbistatin-induced chaotic electrical activities in isolated rat atrium preparations - Natnicha Kanlop (2018)
We have studied the spatiotemporal pattern of blebbistatin-induced anomalous electrical activities in isolated rat atrial preparations using the optical mapping of excitation spread. Atrial preparations including the right or left auricle were dissected from adult rat hearts. Each preparation was then stained with a fast merocyanine-rhodanine voltage-sensitive dye (NK2761). Using a multi-element (16 × 16) photodiode array, we assessed the spread of excitation optically by timing the initiation of the action potential-related extrinsic absorption changes. The contraction-related optical signals were suppressed by adding (S)-(-)-blebbistatin (10-100 μM) to the bathing solution. Blebbistatin had an effective delay time of about 1.5 h following its application, at which time anomalous electrical activities occurred. These took the form of triggered activities and rhythmical spontaneous excitations. We optically mapped the spatiotemporal patterns of the excitation spread during these anomalous electrical activities. When the triggered activities occurred, the site of ectopic focus, where the triggered action potential first appeared, and the area of excitation spread varied in every event. When the rhythmical spontaneous excitations occurred, the excitation spread from the anomalous pacemaker and, occasionally, their spatial shift was observed. In addition, the combination pattern of the spontaneous excitations and triggered activities was also observed. We suggest that these phenomena are due to the disturbed intracellular calcium dynamics induced by the application of blebbistatin. © 2009 The Physiological Society of Japan and Springer.